Urgensi Audit Delay: Antara Total Asset, Profitabiltas dan Fee Audit Pada Perusahaan Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia - Bahtiar Effendi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
This study aims to determine the effect of total assets, profitability and audit fees on audit delay of manufacturing industry companies listed on the Indonesian stock exchange. This study uses a quantitative approach. The data collection technique used in this study is the documentation method, which is by collecting and recording financial statements. The data source used is secondary data in the form of financial statements of manufacturing industry companies listed on the Stock Exchange for the period 2016-2018 which can be obtained through the site www.idx.co.id. The sampling technique used was purposive sampling with 39 units of data analysis. The data analysis method used is multiple linear regression analysis using the SPSS 24.0 program. The results showed that (1) total assets had a significant positive effect on audit delay of manufacturing industry companies listed on the Indonesia Stock Exchange. (2) Profitability has a negative or no significant effect on audit delay of manufacturing industry companies listed on the Indonesia Stock Exchange, (3) Audit fee has a significant positive effect on audit delay of manufacturing industry companies listed on the Indonesia Stock Exchange.